We are the luckiest : the surprising magic of a sober life - McKowen, Laura, 1977- (New World Library, 2020)
"A memoir of alcohol addiction and recovery, written by a successful career woman who describes the joys and challenges of staying sober in a culture permeated by drinking."--Provided by publisher